Peculiarities of distribution of HLA class I antigens in patients with lihen planus - Irina I. Zakhur; Sergei V. Koshkin; Galina A. Zaitseva; Varvara A. Bobro (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
The article presents data on the distribution characteristics of the HLA class I system antigens in patients with lichen planus. Aim. To study the patterns of distribution of HLA class I antigens in the general group. To establish the presence of an association of the disease with antigens of the HLA class I. Material and methods. Laboratory analysis of the distribution of HLA class I antigens was carried out in 60 patients with various forms of lichen planus who consider themselves Russian on the basis of linguistic and ethnicity. The duration of the disease is 120 years. Results. When analyzing the typing results in the general group of patients; a tendency to negative association of HLA-A11 and HLA-B7. It was found that the frequency of haplotype combinations A1-B8; A2-B27; A2-B40; A3-B35 significantly exceeded that of healthy people. Analysis of the frequency of phenotypic combinations revealed a significant increase in A3-A19 and B12-B35. Conclusion. Haplotype and phenotypic combinations of HLA A1-B8; A2-B27; A2-B40; A3-B35; A3-A19; B12-B35 are provoking factors in the development of various forms of the disease. The presence of these genetic traits in the individual increases the risk of developing lichen planus by 311 times. In turn; the HLA-A11 and B7 antigens play a protective role.